2022
DOI: 10.1109/jeds.2021.3132429
|View full text |Cite
|
Sign up to set email alerts
|

Study of Current Collapse Behaviors of Dual-Gate AlGaN/GaN HEMTs on Si

Abstract: Surface traps on GaN-based HEMTs (high-electron-mobility transistors) usually result in the increase of channel on-resistance. It becomes worsen when short pulses are applied during high-frequency and high voltage switching. Here we present a dual-gate transistor structure to suppress the dynamic on-resistance increase. The auxiliary gate under a proper fixed voltage is able to induce additional electrons to compensate the channel carrier loss during main gate switching, leading to a lower dynamic on-resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As we know the current collapse behavior in the GaN HEMT is related to the trap states, the larger the normalized dynamic R on , the more serious the current collapse. [27][28][29][30] The significant decrease of the dynamic R on is observed as the drain voltage increases in samples, in comparison, the dynamic R on of sample A and sample B are 1.5 and 1.1 times higher than the static R on after OFF-state V DS stresses at 400 V, respectively, it indicates that sample B has a smaller current collapse effect.…”
mentioning
confidence: 88%
“…As we know the current collapse behavior in the GaN HEMT is related to the trap states, the larger the normalized dynamic R on , the more serious the current collapse. [27][28][29][30] The significant decrease of the dynamic R on is observed as the drain voltage increases in samples, in comparison, the dynamic R on of sample A and sample B are 1.5 and 1.1 times higher than the static R on after OFF-state V DS stresses at 400 V, respectively, it indicates that sample B has a smaller current collapse effect.…”
mentioning
confidence: 88%
“…Small signal gain comparison shown in table 2 explains the suitability of dual-FP structure. The carrier distribution in the channel region provides insight into the enhancement made possible by the dual-gate configuration [87].…”
Section: Current Collapse Suppressionmentioning
confidence: 99%
“…Previously, we demonstrated that the DG GaN HEMTs could effectively suppress the current collapse phenomenon [15]. The fixed voltage at the additional gate electrode attracts extra electrons to compensate depleted carriers due to current collapse.…”
Section: Introductionmentioning
confidence: 99%